2016
DOI: 10.4314/afrrev.v10i2.9
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Concept Mapping Instructional Strategy in Remedying Students' Problem-Solving Difficulties in Stoichiometry

Abstract: Concept mapping strategy has been found to be effective in science education. However, its comparative effect in remedying male and female students' problemsolving difficulties in stoichiometric tasks has not been documented. The study aimed at finding the role of concept mapping in remedying students' problem-solving AFRREV, 10 (2), S/NO 41, APRIL, 2016 145 Copyright © IAARR, 2007-2016 difficulties in stoichiometry. The pre-test-post-test-control group design was employed. 60 male and female students were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The pedagogical implication of this finding is that concept map graphic organizer can be used in classrooms that have both male and female students. This finding is consistent with that of Gongden and Delmang (2016) who reported that there was no significant difference in the performance of male and female students' when taught chemistry using concept mapping instructional strategy.…”
Section: Research Questionsupporting
confidence: 91%
See 1 more Smart Citation
“…The pedagogical implication of this finding is that concept map graphic organizer can be used in classrooms that have both male and female students. This finding is consistent with that of Gongden and Delmang (2016) who reported that there was no significant difference in the performance of male and female students' when taught chemistry using concept mapping instructional strategy.…”
Section: Research Questionsupporting
confidence: 91%
“…Contrarily, Veloo, Lee, Seung, (2015) submitted that male students achieved better in chemistry than their female equivalents. However, Gongden and Delmang (2016) and Chawla and Singh (2015) posited that male and female students do not differ in their achievement in chemistry when taught using concept map. Hence, there is no conclusive evidence on the influence of gender on students' achievement in chemistry especially in the use of graphic organizers.…”
Section: Figure 1 Forms and Patterns Of Advance Organizersmentioning
confidence: 98%